Redescription of the last instar larva and pupa of Bezzia roldani (Diptera: Ceratopogonidae) Redescripción del último estadio larval y de la pupa de Bezzia roldani (Diptera: Ceratopogonidae) - Maria M. Ronderos; Gustavo R. Spinelli; Florentina Diaz (Revista de la Sociedad Entomológica Argentina, 2007)
The fourth instar larva and pupa of Bezzia roldani Spinelli & Wirth is redescribed and illustrated by using phase-contrast microscope and scanning electron microscope. Immatures were collected by placing floating hydrophytes of the genera Lemna, Wolfia, Wolfiella and Spirodella (Lemnaceae) in Berlesse funnels. The hydrophytes were collected in the Chascomús and Los Talas ponds, both in the province of Buenos Aires, Argentina. The larva show features typical of carnivorous larvae, and it is compared with that of B. nobilis (Winnertz) and with a similar species of the genus Palpomyia Meigen, P. guarani Lane. The pupa is compared with its similar congener B. blantoni Spinelli & Wirth. Se redescribe e ilustra el último estadio larval y la pupa de Bezzia roldani Spinelli & Wirth, utilizando microscopio de contraste de fase y microscopio electrónico de barrido. Los estados inmaduros se capturaron con la ayuda de embudos Berlesse a partir de hidrófitas flotantes, de los géneros Lemna, Wolfia, Wolfiella y Spirodella (Lemnaceae) de las lagunas Chascomús y Los Talas, ambas en la provincia de Buenos Aires, Argentina. La larva presenta las características típicas de larvas carnívoras, se compara con la de Bezzia nobilis (Winnertz) y con una especie similar del género Palpomyia Meigen, P. guarani Lane. La pupa se compara con la de Bezzia blantoni Spinelli & Wirth.